Can you conclude that $A = B$ if $A$, $B$, and $C$ are sets such that

(a) $A \cup C = B \cup C$

No, the sets $A=\{1,2\}, B=\{3,4\}, C=\{1,2,3,4,5\}$ disprove this, because $A \cup C = B \cup C$ but $A\neq B$

(b) $A \cap C = B \cap C$

No, the sets $A=\{1,2\}, B=\{1,4\}, C=\{1\}$ disprove this because $A \cap C = B \cap C=\{1\}$, however $A\neq B$

(c) $A \cup C = B \cup C$ and $A \cap C = B \cap C$

Having Trouble with (c)

This is what I have based on your response

L1 A ∪ C = B ∪ C
L2 A ∩ C = B ∩ C
L3 ∀x(x ∈ A ∪ x ∈ C = x ∈ B ∪ x ∈ C    )    
L4 ∀x(x ∈ A ∪ x ∈ C = x ∈ B ∪ x ∈ C    )    
L5 ∀x(x ∈ A ∩ x ∈ C = x ∈ B ∩ x ∈ C)
L6 ∀x(x ∈ A ∩ x ∉ C = x ∈ B ∩ x ∉ C)

We are given sets $A,B$ and $C$ such that $A \cup C = B \cup C$ and $A \cap C = B \cap C$. We wish to conclude $A = B$.

To show $A = B$ it suffices to show $A \subseteq B$ and $B \subseteq A$. I will go through one of these arguments leaving you to show the other.

So, let's show that $A \subseteq B$, i.e. for every $a$ in $A$ we have $a$ in $B$:

Since $a \in A$ and $A \subseteq A \cup C$ it follows that $a \in A \cup C$. Now since $A \cup C = B \cup C$ if follows that $a \in B \cup C$.

Ok, now we ask a question, is $a$ in $C$? Well, it might be or it might not be. But either it is in $C$ or it is not. So there are two cases:

1.) Suppose $a$ is in $C$. Then $a$ is in $A$ and $C$, i.e. $a \in A \cap C$. Since $A \cap C = B \cap C$ (by our assumption) it follows that $a \in B \cap C$, in particular $a$ is in $B$.

2.) Suppose $a$ is not in $C$. Ok, well, we know that $a$ is in $B \cup C$, so if $a$ is not in $C$ then it must be in $B$.

Thus, in both cases $a$ is in $B$, which is exactly what we wanted. Thus we have shown $A \subseteq B$.

Now you must use a similar argument to show that $B \subseteq A$. When you have this, it follows (by definition of set-equality) that $A = B$.

  • $\begingroup$ Hmm i appreciate the quick response... but idk, i think the equals signs are throwing me off? this is what I have L1 A ∪ C = B ∪ C _______ L2 A ∩ C = B ∩ C _______ L3 ∀x(x ∈ A ∪ C = B ∪ C) ______ L4 ∀x(x ∈ A ∪ C = x ∈ B ∪ C)______ $\endgroup$ – user155456 Jun 5 '14 at 19:43
  • $\begingroup$ ok, I'm not sure I understand your difficulty, but I edited a bit and gave the beginning of an argument. Has this helped? $\endgroup$ – user50948 Jun 5 '14 at 19:47
  • $\begingroup$ should I be trying to get rid of the C's somehow? I guess that's what I'm confused about, im not sure where providing that 'a' is an element of A and B is going to get me? If i say a a∉C, then wouldn't I just be running in circles changing all of the other elements to ∉? Sorry dude I'm very much a noob to this stuff. Edited to show my 'progress' $\endgroup$ – user155456 Jun 5 '14 at 19:56
  • $\begingroup$ Ok, no problem, try and read through my edited version. $\endgroup$ – user50948 Jun 5 '14 at 20:10

Let it be that $A\cup C=B\cup C$ and $A\cap C=B\cap C$ and assume that $a\in A\wedge a\notin B$.

Then $a\in A\cup C=B\cup C$ and $a\notin B$ tells us that $a\in C$.

However, then $a\in A\cap C=B\cap C\subset B$ and a contradiction is found.

We conclude that $\forall x\;\left[x\notin A\vee x\in B\right]$ or equivalently $A\subseteq B$.

Likewise we find $B\subseteq A$ hence $A=B$.


We know $A = B$ iff both the following: $$x \in A \implies x \in B\\ x \in B \implies x \in A $$

We also know $$ x\in A \implies x \in A\cup C $$ $$ x \in A\cap C \implies x \in A, x\in C $$ $$ \begin{align} x\in A \cup C \implies &x \in A, \text{or}\\ &x\in C \end{align} $$ which transposes to: $$ x\not\in C \implies (x\in A\cup C \implies x \in A) $$

We assume: $$ A\cap C = B \cap C,\\ A\cup C = B\cup C $$

Select $x \in A$. Then either $x\in C$ or $x\not\in C$.

  1. $x\in C$: $$ \begin{align} x\in A,x\in C &\implies x\in A\cap C\\ &\implies x\in B\cap C\\ &\implies x\in B \end{align} $$

  2. $x\not\in C$ $$ \begin{align} x\in A &\implies x\in A\cup C\\ &\implies x\in B\cup C\\ x\not\in C,x\in B\cup C &\implies x\in B \end{align} $$

In either case, $x\in A \implies x\in B$. The arguments work the same with $A$ and $B$ switched, so $x\in B \implies x\in A$. Thus, we conclude $A=B$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.